PO 8564 What is clinical trial quality? A qualitative study based on interviews with different stakeholders conducting clinical trials in sub-saharan africa. (24th April 2019) - Lazarova, Angela; Fuchs, Claudia; Burri, Christian
Abstract : Background: There is no unified, broad definition for quality in clinical trials (CTs). Besides the explicit quality requirements in international guidelines and national legislation, however, there are broader factors to consider, including specific setting-related aspects influencing quality needs, quality perception and local implementation of guidelines. Our objective was to identify these factors from a resource-limited settings perspective (in this case, sub-Saharan Africa). Methods: In March-April 2018, we conducted a qualitative study based on semi-structured interviews with participants from three stakeholder groups (monitors, sponsors, and investigators) conducting CTs in sub-Saharan Africa. We identified the interviewees either through CT registry platforms, a web search or by reference. We aimed to include 10–20 participants per stakeholder group. After consent, the interviews were held in person (via Skype or telephone), recorded, and transcribed verbatim. The interview questionnaire addressed a CT quality definition and quality factors during the CT process. We performed the analysis using the framework method. Results: So far, we included 21 participants (17 investigators, two sponsors, two monitors). Eight (8) (from sub-Saharan Africa) and 13 (not from sub-Saharan Africa) who contributed to CTs in 19 different countries in sub-Saharan Africa. Quality definitions mentioned so far were variable. A repeated statement was that the quality definition should be broad and include a system of multiple aspects and layers. We will interview more experts with sponsor and monitor experience in May 2018 and elaborate these quality aspects and layers. We will discuss these results with regards to a comprehensive quality framework for CTs currently under development for Northern countries by another Swiss research team. Conclusion: CT quality was perceived in variable ways, as was the relevance of the aspects across different CT steps. Structuring the multifaceted layers of CT quality will facilitate appropriate and efficient CT quality management in sub-Saharan Africa.